Hepatic vascular hamartoma in a cat: a case report with literature review - Negoescu, Andrada; Gal, Claudiu; Bărbulescu, Andra; Vulcan, Elena; Rădulescu, Alice; Cătoi, Cornel; Taulescu, Marian (Frontiers in Veterinary Science, 2024)
Vascular hamartomas represent a focal proliferation of disorganized vascular tissue, which is usually present at birth. An 8-month-old Scottish fold female cat presented with abdominal distention, mild dyspnea, pale mucous membranes, and lethargy. Ultrasound examination revealed a hepatic mass resembling multiple cysts affecting the right medial lobe. Surgical excision was performed, and tissue samples were sent for histopathological evaluation. The mass was composed of multiple, dilated, variably-sized well-differentiated arterioles and venules, consistent with vascular hamartoma. Immunohistochemical investigation of the cells lining the cystic structures showed positive immunolabeling for vimentin and negative immunolabeling for PanCK, supporting the histological diagnosis. Based on existing literature, this represents the first case of hepatic localization of vascular hamartoma in a cat. In addition, a comparative histological study between vascular hamartoma and biliary duct hamartoma and a review on hepatic vascular hamartomas in animals and hepatic cystic masses in cats was made.